The family in crisis: an analysis of the home spaces in a selection of contemporary Nigerian novels in English - Cowin, Bettina (Sächsische Beiträge zur Literatur- und Ideengeschichte, 2025)
"To examine the nature of the home spaces described in three twenty-first-century Nigerian novels in English, a selection of spatial theories was applied. These contemporary novels all depict family life and are set in different areas of Nigeria, a postcolonial country encompassing diverse ethnic backgrounds, including Igbo, Yoruba and Hausa environments. Despite these regional and cultural differences, all the homes presented in the novels are concerned with families in a state of crisis. Examining these novels in their social and historical context using spatial theory, reasons for the manifest dysfunctionality of the families were considered. A further objective was to explore whether the strictly hierarchized patriarchal structures in many of the family homes correspond to similar structures on the macro-level of the country. Additionally, the aim was to examine to what extent the oppressive political and social situation of the postcolonial country as a whole percolates down into the heterogenous domestic situations of these groups"--
Includes bibliographical references
Keywords: Nigeria -- In literature; Hochschulschrift; Innenraum; Familienroman; Englisch; Nigeria